Recent Progress in the Characterization of the Atmosphere of Exoplanets: Observations, Models - Imad Kamil Zayer (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Characterizing exoplanet atmospheres has become a major focus of modern astrophysics to understand the composition, structure, and evolution of planets beyond the Solar System. Specific Background: Advances in observational instruments, spectroscopy techniques, and atmospheric modeling especially with next-generation telescopes such as the James Webb Space Telescope have expanded the capability to study planetary atmospheres. Knowledge Gap: However, challenges remain in interpreting atmospheric spectra due to retrieval degeneracies, stellar contamination, and limitations in cloud and chemical modeling. Aims: This review summarizes recent developments in observational techniques and atmospheric analysis used in exoplanet research. Results: Recent observations have detected molecules such as H₂O, CO₂, CH₄, Na, K, and SO₂, while improved spectroscopic methods allow investigation of atmospheric circulation, thermal structure, disequilibrium chemistry, and atmospheric escape. Novelty: The study integrates recent observational and modeling progress that advances atmospheric characterization techniques. Implications: These developments support deeper understanding of planetary diversity and strengthen the search for habitable environments and biosignatures beyond Earth. Highlights:• Multi-method spectroscopic observations reveal molecular composition and atmospheric structure of distant planets.• Next-generation telescopes provide broader wavelength coverage enabling detection of trace gases.• Modern retrieval algorithms integrate machine learning and radiative transfer modeling for spectral interpretation. Keywords: Exoplanet Atmospheres, Atmospheric Spectroscopy, James Webb Space Telescope, Transmission Spectroscopy, Planetary Science